Leptospirosis: A new perspective on an old disease - Olson, Jerry (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Disease causing Leptospira can be placed in one of two broad categories for common domesticated mammals: They are either hostadapted or incidental strains. The four incidental serovars of Leptospira that are pathogenic to cattle are: L. pomona, L. grippotyphosa, L. canicola and L. icterhemmorhagiae. They are transmitted to cattle from other carrier animals that act as hosts for these strains. The strains are found in chronically infected rats, dogs, deer, or even pigs and are transmitted to cattle though urine-contaminated water. When the incidental strains of Leptospira are introduced into an unvaccinated, susceptible herd of cattle, they commonly cause an outbreak of abortions in the mid- to late-term pregnant cows. Commercial five-way Leptospiral vaccines are effective in preventing the abortion storms associated with the incidental strains of Leptospira, but ineffective to the most common serovar found in cattle (hardjo-bovis). Pfizer Animal Health recently received USDA approval to market the first effective L. hardjo vaccine, known as Spirovac®, in the United States.
Keywords: Dairy; Lepto hardjo; Health